Increasing Students’ Vocabulary Mastery Through English Movie At Senior High School In Gowa - Sebastianus Torino Shandri; Muliaty Ibrahim; Sukmawati (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2024)
The objective was to determine the influence of English movie to improve students’ vocabulary mastery. This used a quantitative research with experimental method. This study used two classes, namely experimental class with English movie and control class without English movie. The samples were grade X IPA 2 with 30 students for the experiment class and grade X IPA 3 with 30 students for the control class.Data collection techniques were pre-test and post-test. The results indicated the pre-test result mean value in the experimental class was 38.50 and the pre-test in the control class was 34.17 indicating that the students ability in the pre-test was still very low while the experimental class mean value in post-test was.83.17 and the post test results in the control class were 63.17 showing that the students’ vocabulary mastery was in a good category and began to increase. The data were analyzed by using and independent sample of normality that 0.053 >0.05 so that normality is distributed, homogeneity values are met,t-test,indicating that Sig.( 2-tailed) is 0.000 lower than 0.05 so that the influence is found. The research proves there is an increase in the students’ vocabulary mastery trough English movie.It can be concluded that English movie can improve the vocabulary mastery of grade X IPA 2 students at SMAN 10 GOWA.